Will social participation make retirees happier? An empirical study about retirement life in China - Zhao, Luman; Yu, Jia (Journal of Applied Business and Economics, 2025)
How elderlies participate in social activities is a key issue in coping with aging and has an important impact on elderlies’ well-being. This paper examines the effects of different social participation patterns on the happiness of the elderlies in China. The empirical analysis was conducted based on the data from the China Household Finance Survey (CHFS) in 2015. The research results show that compared with reemployment after retirement, community governance is a more common way for retired people to be involved in social activities. We found that reemployment significantly reduces the happiness degree of the retired. Furthermore, this negative effect is more significant in samples without a formal labor contract, relatively lower education level, & senior retired people. In contrast, participating in community governance can significantly improve the happiness level of retirees, which is more essential in the sample of the medium education level and junior retirees.
Keywords: Business; China; Demographic economics; Economics; Empirical research; Labour economics; Life satisfaction; Political science; Psychology; Social psychology; dept.eco

Joining farmers’ cooperatives leads to equitable poverty reduction in China – empirical evidence from the rural households survey - Zhang, Ze; Qin, Lijian; Jia, Yu; Li, Yuheng; Hong, Chen; Qin, Wenshuai (Applied Economics, 2025)
Keywords: China; Empirical evidence; Inequality; Poverty; Poverty reduction; Rural poverty; Survey data collection; dept.eco